1985
DOI: 10.1128/jb.162.1.9-20.1985
|View full text |Cite
|
Sign up to set email alerts
|

High state of order of isolated bacterial lipopolysaccharide and its possible contribution to the permeation barrier property of the outer membrane

Abstract: The conformational properties of the isolated S form of Salmonella sp. lipopolysaccharide (LPS), of Re mutant LPS, and of free lipid A were investigated by using X-ray diffraction and conformational energy calculations. The data obtained showed that LPS in a dried, in a hydrated, and probably also in an aqueous dispersion state is capable of forming bilayered lamellar arrangements similar to phospholipids. From the bilayer packing periodicities, a geometrical model of the extensions of the LPS regions lipid A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(74 citation statements)
references
References 52 publications
8
66
0
Order By: Relevance
“…The influence of the presence of Kdo-linked L-Arap4N might not only be due to the electrostatic repulsion between the positive charges of i.-Arap4N and polymyxin B, but also to the sterical availability of the carboxyl-groups of the Kdo units. It has been reported that the lipid A backbone is orientated in a 45 ° angle relative to the outer membrane surface and that the resulting free space is filled with Kdo residues of the inner core region which may then lead to an exposure of free carboxyl groups of the Kdo residues [31,32]. This model confirms the assumption that these carboxylic-groups represent, probably together with ester-linked lipid A-phosphate group, the primary binding site of polycationic molecules such as polymyxins.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of the presence of Kdo-linked L-Arap4N might not only be due to the electrostatic repulsion between the positive charges of i.-Arap4N and polymyxin B, but also to the sterical availability of the carboxyl-groups of the Kdo units. It has been reported that the lipid A backbone is orientated in a 45 ° angle relative to the outer membrane surface and that the resulting free space is filled with Kdo residues of the inner core region which may then lead to an exposure of free carboxyl groups of the Kdo residues [31,32]. This model confirms the assumption that these carboxylic-groups represent, probably together with ester-linked lipid A-phosphate group, the primary binding site of polycationic molecules such as polymyxins.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides used in this study (Table 1) can be divided in three groups: group A, based on the human lactoferricin sequence (Lfcin H), group B, based on the bovine lactoferricin sequence (Lfcin B) and group C, comprising the more active tritrpticin and tritrpticin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Peptides were synthesised by Advanced Biotechnology Centre (ABC) (Imperial College London) using an automatic synthesiser and analysed by HPLC.…”
Section: Cationic Peptidesmentioning
confidence: 99%
“…Their modes of action can vary and are not fully understood, but their main site of action is thought to be the cell membrane. The enterobacterial OM bilayer consists of an inner monolayer containing phos-pholipids and an outer monolayer that is mainly lipopolysaccharide (LPS) [3].…”
Section: Introductionmentioning
confidence: 99%
“…A core oligosaccharide region (R-core) covalently bridges a lipid anchored to the outer leaflet of the phospholipid bilayer (lipid A) with a side chain composed of a number of repeating oligosaccharide units (O-chain) (Wilkinson 1996;Nikaido 2003). LPS is thought to be an endotoxin in animal immune systems (Ulevitch and Tobias 1995;Raetz and Whitfield 2002), is a permeation barrier against exogenous lipophilic toxins (Labischinski et al 1985;Nikaido 2003) and provides membrane structural integrity (Skurnik et al 1999;Walsh et al 2000) and cellular adhesion or recognition (Paradis et al 1994;Shapiro et al 1997). However, some evidence suggests that LPSs in cyanobacteria are structurally and functionally different from well-studied proteobacteria (Hoiczyk and Hansel 2000;Snyder et al 2009).…”
Section: Introductionmentioning
confidence: 99%